The Improved Generalized tanh-coth Method Applied to Sixth-Order Solitary Wave Equation - M. Torvattanabun; J. Simmapim; D. Saennuad; T. Somaumchan (Journal of Mathematics)
The improved generalized tanh-coth method is used in nonlinear sixth-order solitary wave equation. This method is a powerful and advantageous mathematical tool for establishing abundant new traveling wave solutions of nonlinear partial differential equations. The new exact solutions consisted of trigonometric functions solutions, hyperbolic functions solutions, exponential functions solutions, and rational functions solutions. The numerical results were obtained with the aid of Maple.